Analysis of the spatial pattern and causes of ecological environmental quality in Myanmar based on the RSEI model and the Geodetector-GCCM method - Shuangfu Shi; Shuangfu Shi; Shuangyun Peng; Shuangyun Peng; Zhiqiang Lin; Zhiqiang Lin; Bangmei Huang; Dongling Ma; Dongling Ma; Ziyi Zhu; Ziyi Zhu; Yilin Zhu; et al. (Frontiers in Environmental Science)
Facing the challenges brought about by global climate change and biodiversity loss, accurately assessing ecological environmental quality (EEQ), and its driving factors are crucial for formulating effective strategies for ecological protection and restoration. However, there remains limited understanding of the interactions and causal relationships between multiple factors, with existing studies mainly focusing on the impact of individual factors on EEQ and their correlations. This study took Myanmar as the research area, employing a Remote Sensing Ecological Index (RSEI) model and spatial autocorrelation analysis to quantitatively evaluate the spatial distribution characteristics of Myanmar’s EEQ in 2020 and reveal its spatial dependence. Furthermore, by innovatively integrating the Geodetector and Geographical Convergent Cross Mapping (GCCM) methods, this study systematically analyzed the impacts and causal relationships of various factors on the spatiotemporal differentiation of EEQ. The results indicate that: (1) Myanmar’s overall EEQ was relatively good, but there is significant spatial heterogeneity; (2) Local spatial autocorrelation analysis revealed a clear spatial clustering pattern of EEQ in Myanmar; (3) Geodetector analysis identified DEM, slope, Net Primary Productivity (NPP), land use, and human footprint as the dominant factors influencing EEQ, with significant interactions among these factors; (4) GCCM analysis further verified the significant causal effects of DEM, slope, NPP, and human footprint on EEQ, while the causal effects of temperature, precipitation, and land use are relatively weaker. This study established a technical framework for analyzing the spatial differentiation and causes of EEQ, unveiling the mechanisms of ecological evolution driven by natural and human factors. It enriched the understanding of human-environment interactions within coupled systems and delved into the complex mechanisms and causal effects among multiple factors within the ecological system. These insights enhanced our understanding of the intricate relationships between EEQ and its influencing factors, providing valuable references for ecological protection and sustainable development in Myanmar.